Distinct oncogenes drive different genome and epigenome alterations in human mammary epithelial cells. Issue 5 (10th June 2019) - Fonti, Claire; Saumet, Anne; Abi‐Khalil, Amanda; Orsetti, Béatrice; Cleroux, Elouan; Bender, Ambre; Dumas, Michael; Schmitt, Emeline; Colinge, Jacques; Jacot, William; Weber, Michael; Sardet, Claude; et al.
Abstract : Molecular subtypes of breast cancer are defined on the basis of gene expression and genomic/epigenetic pattern differences. Different subtypes are thought to originate from distinct cell lineages, but the early activation of an oncogene could also play a role. It is difficult to discriminate the respective inputs of oncogene activation or cell type of origin. In this work, we wished to determine whether activation of distinct oncogenic pathways in human mammary epithelial cells (HMEC) could lead to different patterns of genetic and epigenetic changes. To this aim, we transduced shp53 immortalized HMECs in parallel with the CCNE1, WNT1 and RASv12 oncogenes which activate distinct oncogenic pathways and characterized them at sequential stages of transformation for changes in their genetic and epigenetic profiles. We show that initial activation of CCNE1, WNT1 and RASv12, in shp53 HMECs results in different and reproducible changes in mRNA and micro‐RNA expression, copy number alterations (CNA) and DNA methylation profiles. Noticeably, HMECs transformed by RAS bore very specific profiles of CNAs and DNA methylation, clearly distinct from those shown by CCNE1 and WNT1 transformed HMECs. Genes impacted by CNAs and CpG methylation in the RAS and the CCNE1/WNT1 clusters showed clear differences, illustrating the activation of distinct pathways. Our data show that early activation of distinct oncogenic pathways leads to active adaptive events resulting in specific sets of CNAs and DNA methylation changes. We, thus, propose that activation of different oncogenes could have a role in reshaping the genetic landscape of breast cancer subtypes. Abstract : What's new? Different molecular subtypes of breast cancer generally are assumed to arise from different cell lineages, though other activating factors may also be involved. Here, using engineered primary human mammary epithelial cell (HMEC) models, the authors show that founding oncogenic mutations that activate distinct cancer‐promoting pathways impact the molecular landscape of breast tumors. HMEC transformation induced by distinct oncogenes resulted in different, reproducible patterns of copy number aberrations and changes in DNA methylation. The findings indicate that phenotypic characteristics of tumors and their genomic and epigenetic profiles are strongly impacted by the early activation of oncogenic pathways.